"Bringing Your Full Self to Work": Fashioning LGBTQ Bankers on Wall Street. (21st June 2022) - Kaplan, Spencer
Abstract: This paper examines the project of US corporate diversity and inclusion as it is experienced by LGBTQ‐identified employees on Wall Street. It draws on ethnographic research among junior bankers who participate in Wall Street's LGBTQ recruitment events and employee networks. Attending to their claims that queer difference affords them valuable workplace skills, this paper situates these claims within the gendered ideals of Wall Street, models of entrepreneurial selfhood, and ethical projects of self‐fashioning. It argues that diversity and inclusion is not simply a novel means for corporations to extract value from workers. On Wall Street, LGBTQ bankers use diversity and inclusion to, as they say, "bring their full selves to work" and fashion themselves as queer and financial subjects. Starting from their first experiences at the banks' recruitment events, they are incited to pursue this project of self‐fashioning by exemplary senior LGBTQ leaders. They learn that by managing queer difference as human capital today, they can achieve professional success in the future. In pursuit of this payoff, they engage with queer difference as an object of speculation.